2013
DOI: 10.1089/neu.2012.2353
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase, Chondroitinase ABC, and Combination Therapy after Spinal Cord Contusion Injury

Abstract: Axon regeneration in the central nervous system is severely hampered, limiting functional recovery. This is in part because of endogenous axon regeneration inhibitors that accumulate at the injury site. Therapeutic targeting of these inhibitors and their receptors may facilitate axon outgrowth and enhance recovery. A rat model of spinal cord contusion injury was used to test the effects of two bacterial enzyme therapies that target independent axon regeneration inhibitors, sialidase (Vibrio cholerae) and chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…ChABC acts on chondroitin 4-suphate, chondroitin 6-sulphate, and dermatan sulfated proteogycans, and acts very slowly on hyaluronate. This enzyme has been used to promote axon regeneration in lesioned spinal cord in single and combined treatments (e.g., [34,[53][54][55]). In fact, ChABC has been used in combination with OECs [32,56], and the expression of ChABC has also been directed to Schwann cells [57] and astrocytes [58] with relevant results.…”
Section: Reduced Migration and Traction Forces In Cultured Teg Cells mentioning
confidence: 99%
“…ChABC acts on chondroitin 4-suphate, chondroitin 6-sulphate, and dermatan sulfated proteogycans, and acts very slowly on hyaluronate. This enzyme has been used to promote axon regeneration in lesioned spinal cord in single and combined treatments (e.g., [34,[53][54][55]). In fact, ChABC has been used in combination with OECs [32,56], and the expression of ChABC has also been directed to Schwann cells [57] and astrocytes [58] with relevant results.…”
Section: Reduced Migration and Traction Forces In Cultured Teg Cells mentioning
confidence: 99%
“…The enzymes chondroitinase (ChABC) (for review see [148] ) and sialidase [149,150] , or a combination of the two were shown to decrease growth inhibition [151] . Many groups have shown that administration of ChABC is associated with sensory axonal regeneration [152] and functional recovery [148,152,153] when experimentally introduced following SCi.…”
Section: Functionalizing Biomaterials To Tip the Balancementioning
confidence: 99%
“…Many groups have shown that administration of ChABC is associated with sensory axonal regeneration [152] and functional recovery [148,152,153] when experimentally introduced following SCi. When comparing the two, one group found that sialidase increases axonal regeneration and functional recovery [149][150][151] to a greater degree than either ChABC alone or a sialidase/ChABC combination [151] .…”
Section: Functionalizing Biomaterials To Tip the Balancementioning
confidence: 99%
See 1 more Smart Citation
“…ChABC was found to improve function after dorsal lesions of cervical spinal cord (Bradbury et al 2002). In cases of other SCI models, treatment with ChABC alone improved axonal sprouting, although it induced little or no recovery of locomotor function after hemisection (Alilain et al 2011;Hunanyan et al 2010) and contusion (Harris et al 2010;Mountney et al 2013;Tom et al 2009). …”
Section: Chabc/aav-nt3 Treatmentmentioning
confidence: 99%